Análise de parâmetros relevantes para a armazenagem e deposição de combustíveis irradiados de sistemas nucleares inovadores - Jean Anderson Dias Salomé (2016)
Considering a scenario of fourth generation reactors and hybrid systems, studies that analyze the composition of irradiated nuclear fuels are essential, because in addition to investigate the evolution of the material, they can determine the presence and quantity of the most important isotopes for understanding of the most significant radiotoxic and thermal effects and the impact of the temporary or permanent disposal of these fuels. In this research, the systems PWR, VHTR with standard fuel, VHTR with reprocessed fuel and a hybrid ADS-Fission system were analyzed and compared until 107 years. Such parameters as the composition, radioactivity, radiotoxicity by ingestion and inhalation and decay heat were evaluated. In the sequence, studies about the criticality and heat transfer of theses spent fuels were carried out inside a temporary repository, and finally, a thermal analysis of the materials into a canister inside a geological repository was done. The PWR reactor was used as standard basis of comparison. The computer code ORIGEN 2.1 was used to perform calculations on the composition and spent fuel decay parameters, emphasizing the contribution of the relevant actinide isotopes and fission products for them. The SCALE 6.0 code KENO V.a module was used to investigate the criticality and, in the thermal analysis, the ANSYS Student code via CFX and Transient Thermal modules. Thus, this work evidenced the great impact of innovative systems on the management of the back-end of the nuclear fuel cycle. The comparison of the calculated results for the fuel of a typical PWR reactor in temporary and permanent repositories with the values found for the fuels from these systems establishes a milestone for the deepening of this theme. From the results it is verified the strong influence of the isotopes of plutonium, minor actinides and fission products on the behavior of the fuels.